Identification and seasonal fluctuations of the mango fruit fly in central Sudan - E, Ahmed, Eman; Elkashif2, M, E; H. He Bashir, N. (Gezira Journal of Agricultural Science; Vol 1 No 2 (2003), 2021)
Field surveys were carried out in Hantoub area, east of Wad Medani, Sudan, during the period from March 1998 to February 1999 to identify the prevailing species of mango fruit fly and to study their seasonal abundance and fluctuation, using yellow dome-shaped taps with attractants (cue-lure and methyl eugenol), and sticky yellow traps. Infestation level and the most susceptible stage of fruit maturity in four tested cultivars (Alphons, Baladi, Shendi and Abu samaka) were studied. The behaviour of the adult fly in the field was observed and the alternative host plants for the pest were also surveyed. The results revealed that Ceratitis cosyra (Walker) was the dominant species of fruit flies in the study area. The peak population of the fly was observed in the humid months of July and August. Alphons cultivar was the least susceptible while Shendi cultivar showed high susceptibility. The ripe stage of the fruit was the most preferred stage for infestation. Guava fruit represented the best alternative host for the pest